Feasibility of a terms bank for small horsepower tractors - Peterson, Colin (Kansas State University, 2015)
The Agriculture Equipment Manufacturing industry is a $42 billion dollar industry in the United States. The Agricultural Equipment industry is very competitive across all market segments, especially in the less than 100 horsepower category (<100hp). This tractor category consists of 4 sub categories: <20hp, 20-40hp, 40-60hp, and 60-100hp. The <100hp tractor segment accounted for 170,547 of the 207,833 tractors that were sold during the 2014 year. Compared to the over 100 horsepower category (100+hp) that has fewer competitors, the <100hp segment is more competitive with more manufacturers competing for market share. Company XYZ is a full line manufacturer of agricultural equipment, harvesters, and construction equipment. Company XYZ lost some ground in market share due to the increased competition from new entrants into the market place as well as established manufacturers increasing their presence. To be more competitive, Company XYZ is looking at industry best practices to see how they can increase market share. One of these practices is a terms bank. A terms bank allows a dealer to stockpile unused months of terms to be used at a later date on tractors with expired terms. This minimizes financial risk for dealers to stock inventory. The cost to stock inventory is a large expense that dealers must carefully manage. One of the biggest costs of stocking inventory is the interest paid for tractors that have exhausted their interest free terms. A terms bank may lower the amount of interest that a dealer pays. It also lowers the cost to stock inventory and allows the dealership to manage and reduce these costs and risks. Evaluating the factors associated with stocking inventory, especially interest rate, will help manage inventory costs and stocking levels. This thesis uses regression analyses to analyze the costs of stocking units and the effect it has on dealership revenues. A regression analysis will test the hypothesis that lowering the interest portion of the cost of stocking inventory will increase sales. Data were gathered for dealership groups in the Western United States on a monthly basis for the years 2008 – 2014. The results supported the hypothesis that lowering the interest rate at dealerships was positively correlated with revenues. The reduced interest cost lowers the carrying cost of inventory and point to a terms bank being an effective tool for increasing Company XYZ’s market share.
Keywords: Small horsepower tractors; Market share; Inventory management; Terms bank; Dealer carrying cost